2013
DOI: 10.1111/j.2041-1626.2012.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of grapefruit, tangerine, lime, and lemon oils as solvents for softening gutta‐percha in root canal retreatment procedures

Abstract: Under the conditions of the present study, grapefruit oil and tangerine oil performed best as gutta-perch solvents among four natural oils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
0
16
0
3
Order By: Relevance
“…Several techniques for filling materials removal are currently used, including manual and rotary instruments, preceded by the softening of the filling material with heat or solvents appropriate for such purpose. [ 4 5 ] However, no retreatment technique is capable of removing the filling material completely; resulting in residual debris attached to the root canal walls after reinstrumentation. [ 4 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques for filling materials removal are currently used, including manual and rotary instruments, preceded by the softening of the filling material with heat or solvents appropriate for such purpose. [ 4 5 ] However, no retreatment technique is capable of removing the filling material completely; resulting in residual debris attached to the root canal walls after reinstrumentation. [ 4 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…For dissolving GP, a nonpolar solvent or less polar solvent must be used. 12 The use of hand files was statistically different from the use of rotary instruments to remove filling material. This probably occurred because of GP plasticization resulting from rotation of the instrument.…”
Section: Discussionmentioning
confidence: 97%
“…[21] It brings about dissolution of GP by penetrating and separating the polymer chains. [22] It is more biocompatible and displays less cytotoxicity than Xylene. [23,24]In our study Xylene was found to possess better dissolution for all types of GP than Orange oil.…”
Section: Discussionmentioning
confidence: 99%